Peranan Kelekatan Aman Pada Ayah Dan Ibu Terhadap Penyesuaian Diri Santriwati - Risnida Muzdalifah; Hemy Heryati Anward; Dwi Nur Rachmah (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
The purpose of this study was to find out whether there was a role of secure attachment to father and mother towards self-adjustment. The subjects in this study were 60 people, which were selected using a cluster random sampling technique. Data were collected using psychological scales including a scale of secure attachment to father, a scale of secure attachment to mother and a scale of self-adjustment. These scales used Likert-Scale model and data were analyzed using multiple linear regression analysis. The results showed that: (1) there was a role of secure attachment to mother towards self-adjustment in female students as indicated by the value of t count > t table (2.319 > 2.002); (2) there was a role of secure attachment to father towards self-adjustment in female students as indicated by the value of t count > t table (2.319 > 2.002); (3) there was no difference between the secure attachment to father and the secure attachment to mother towards the self-adjustment in female students as indicated by F count > F table (7.330 > 3.159). Based on these results, it can be seen that the effective contribution of the secure attachment to father and mother towards the self-adjustment was 20.5%, while the remaining 79.5% was contributed by other factors.